Insights into the P-to-Q conversion in the catalytic cycle of methane monooxygenase from a synthetic model system - Xue, Genqiang (National Academy of Sciences, 2008)
For the catalytic cycle of soluble methane monooxygenase (sMMO), it has been proposed that cleavage of the O–O bond in the (μ-peroxo)diiron(III) intermediate P gives rise to the diiron(IV) intermediate Q with an Fe(2)(μ–O)(2) diamond core, which oxidizes methane to methanol. As a model for this conversion, (μ–oxo) diiron(III) complex 1 ([Fe(III)(2)(μ–O)(μ–O(2)H(3))(L)(2)](3+), L = tris(3,5-dimethyl-4-methoxypyridyl-2-methyl)amine) has been treated consecutively with one eq of H(2)O(2) and one eq of HClO(4) to form 3 ([Fe(IV)(2)(μ–O)(2)(L)(2)](4+)). In the course of this reaction a new species, 2, can be observed before the protonation step; 2 gives rise to a cationic peak cluster by ESI-MS at m/z 1,399, corresponding to the {[Fe(2)O(3)L(2)H](OTf)(2)}(+) ion in which 1 oxygen atom derives from 1 and the other two originate from H(2)O(2). Mössbauer studies of 2 reveal the presence of two distinct, exchange coupled iron(IV) centers, and EXAFS fits indicate a short Fe–O bond at 1.66 Å and an Fe–Fe distance of 3.32 Å. Taken together, the spectroscopic data point to an HO-Fe(IV)-O-Fe(IV) = O core for 2. Protonation of 2 results in the loss of H(2)O and the formation of 3. Isotope labeling experiments show that the [Fe(IV)(2)(μ–O)(2)] core of 3 can incorporate both oxygen atoms from H(2)O(2). The reactions described here serve as the only biomimetic precedent for the conversion of intermediates P to Q in the sMMO reaction cycle and shed light on how a peroxodiiron(III) unit can transform into an [Fe(IV)(2)(μ–O)(2)] core.